Early life stress and physical and psychosocial functioning in late adulthood. - Hanna Alastalo; Mikaela B von Bonsdorff; Katri Räikkönen; Anu-Katriina Pesonen; Clive Osmond; David J P Barker; Kati Heinonen; Eero Kajantie; Johan G Eriksson (PLoS ONE, 2013)
Severe stress experienced in early life may have long-term effects on adult physiological and psychological health and well-being. We studied physical and psychosocial functioning in late adulthood in subjects separated temporarily from their parents in childhood during World War II.The 1803 participants belong to the Helsinki Birth Cohort Study, born 1934-44. Of them, 267 (14.8%) had been evacuated abroad in childhood during WWII and the remaining subjects served as controls. Physical and psychosocial functioning was assessed with the Short Form 36 scale (SF-36) between 2001 and 2004. A test for trends was based on linear regression. All analyses were adjusted for age at clinical examination, social class in childhood and adulthood, smoking, alcohol intake, physical activity, body mass index, cardiovascular disease and diabetes.Physical functioning in late adulthood was lower among the separated men compared to non-separated men (b = -0.40, 95% confidence interval [95% CI]: -0.71 to -0.08). Those men separated in school age (>7 years) and who were separated for a duration over 2 years had the highest risk for lower physical functioning (b = -0.89, 95% CI: -1.58 to -0.20) and (b = -0.65, 95% CI: -1.25 to -0.05), respectively). Men separated for a duration over 2 years also had lower psychosocial functioning (b = -0.70, 95% CI: -1.35 to -0.06). These differences in physical and psychosocial functioning were not observed among women.Early life stress may increase the risk for impaired physical functioning in late adulthood among men. Timing and duration of the separation influenced the physical and psychosocial functioning in late adulthood.